Implementasi Trilogi Penyuluh Agama Islam Secara Berimbang pada Masyarakat Muslim Daerah respen Kota Puruk Cahu - Siti Maryam (CV. Syntax Corporation Indonesia, 2021)
The research is motivated by the condition of the community in the Respen area of the city of Puruk Cahu on the results of the observation that the majority of residents of the Respen area are Muslim, but in realitythe understanding and practice of diversity is still low. This is evidenced of the low ability to recite and to write the Al-quran, the unfulfilled five daily prayers with strong ghiroh is supported with demographic conditions. So that, it needs a problem solving of this matter. Islamic Religious Extension is a Civil Servant (PNS) who is given the full task, responsibility and authority by the authorized official to carry out religious guidance and development education through religious language. The main duties and functions of Islamic extension agents are to become professionals in carrying out counseling tasks, in order to support the process of carrying out this counseling task, there are three functions that can be called the trilogy of Islamic extension functions, namely informative-educative functions, consultative functions and advocative functions. PAI PNS as a leading sector of the Islamic community guidance is deal with complex problems and is required to carry out a fairly heavy mandate, to work as a facilitator of Islamic da'wah so that the religious atmosphere can be expressed and actualized understanding, appreciating and practicing the values of faith and devotion in the context of social life, nation and state. This research is an applicative research with a qualitative descriptive approach that is naturely exploratory. The subjects of this study are Islamic religious extension agents and Muslim communities in the Respen area. While the object of the research is the role of the Islamic Religious Instructor and community understanding of religion. The instruments used are observation and documentation. The results of research showed that civil servant of Islamic religious extension officers played their part in increasing religious understanding of the Muslim community living in the Respen area of Puruk Cahu City.